2018
DOI: 10.1177/2325967118785365
|View full text |Cite
|
Sign up to set email alerts
|

Superior Capsular Reconstruction With a Long Head of the Biceps Tendon Autograft: A Cadaveric Study

Abstract: Background:Several procedures have been proposed to address irreparable rotator cuff (RC) tears with pseudoparalysis. One recently proposed procedure is superior capsular reconstruction (SCR) using a tensor fasciae latae (TFL) autograft.Hypothesis:SCR with a locally available long head of the biceps tendon (LHB) autograft is biomechanically equivalent to SCR using TFL autograft for preventing superior humeral migration and the development of RC arthropathy in patients with irreparable RC tears.Study Design:Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 18 publications
0
54
0
Order By: Relevance
“…TFL autograft, acellular dermal allograft, and long head of the biceps tendon autograft appear to be biomechanically viable options, but further clinical study is clearly needed. 10,15,25,29-32,41,42…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TFL autograft, acellular dermal allograft, and long head of the biceps tendon autograft appear to be biomechanically viable options, but further clinical study is clearly needed. 10,15,25,29-32,41,42…”
Section: Discussionmentioning
confidence: 99%
“…TFL autograft, acellular dermal allograft, and long head of the biceps tendon autograft appear to be biomechanically viable options, but further clinical study is clearly needed. 10,15,25,[29][30][31][32]41,42 The ultimate question remains whether these clinical improvements in PRO and VAS scores are comparable with alternative treatments, such as RTSA or LDT, and whether these early positive outcomes will remain consistent in medium-and long-term studies. A systematic review on RTSA for irreparable MRCT showed an ASES score improvement of 30.8 to 42.1 and a Constant score gain of 28.4 to 35.9.…”
Section: Discussionmentioning
confidence: 99%
“…The biceps tendon has been reported for superior capsular reconstruction, [3][4][5][6] but not often for reconstruction of the superior labrum. However, it is widely recognized the glenoid labrum plays a primary role in anterior 7,8 and posterior shoulder instability.…”
Section: See Related Article On Page 353mentioning
confidence: 99%
“…Han et al, 3 using a cadaveric rotator cuff tear model, found that shoulders in which the biceps was used as the reconstructed superior capsule showed decreased subacromial peak contact pressures and shifted the humeral head inferiorly. El-shaar et al 4 analyzed 5 sets of matched cadaveric shoulders after a massive rotator cuff tear was created in each shoulder. An SCR was performed using a TFL autograft in one of the cadaveric shoulder pairs, and the biceps tendon was used to reconstruct the superior capsule in the matched contralateral shoulder.…”
mentioning
confidence: 99%